E-Banking's Effects on Financial Performance of Nepalese Selected Commercial Banks - Wagle, Sudip (Journal of Economics and Management, 2023)
The overview of e-banking has revolutionized and redefined the ways of banks operating. Internet banking, mobile banking, ATM, Card Services, electronic funds transfer, account-to-account transfer, online bill payments, online statements etc. are now consider as the main contribution for the banks success among their core competencies. However, the banking industry has faced challenge to keep pace with technological developments and innovative products to suit its needs to generate more profits. This paper shows the data of five commercial banks from fiscal year 2016/17 to 2020/21. The objective of the study is to identify whether e-banking services has significantly improved the profitability performance of commercial banks in Nepal with regards to the returns on assets (ROA) and returns on equity (ROE) or not. The descriptive as well as inferential statistical tools has been used by using SPSS version 25 software. This result shows that the independent variables; Mobile Banking, Internet Banking, ATM, Debit Card has insignificant impact on profitability of Nepalese commercial banks in terms of ROA. However, Credit Card has negative but significant impact on profitability. On the other hand, all the variables has found to insignificant impact on the profitability of ROE of the commercial banks. Besides this, various macroeconomic factors such as monetary policy, fiscal policy, IT policy, electric Transaction act, political factors etc. are also the cause of profit growth of commercial banks in Nepal.